2019
DOI: 10.1002/er.4863
|View full text |Cite
|
Sign up to set email alerts
|

The equivalent circuit battery model parameter sensitivity analysis for lithium‐ion batteries by Monte Carlo simulation

Abstract: To enhance the estimation accuracy of battery's state of charge, it is imperative to estimate the battery model parameter. To reduce the calculation efforts, the number of the battery model parameter to be estimated should be less while ensuring the state of charge estimation accuracy. Especially in engineering applications, the calculating ability is usually limited. So, it needs to choose the critical battery model parameter to be estimated. This paper's contributions are as follows: The global sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…As can be seen from the S i values, V oc and R 0 are the two, which have the best identifiability among all the six parameters, establishing sufficient confidence for us to use the estimates of these two parameters in battery diagnostic and control applications. This is also discovered by Guo et al through a global sensitivity analysis of second order ECM parameters . Table further shows that the identifiability of these two parameters tends to be much better in the dynamic operating conditions.…”
Section: Results Analysis and Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…As can be seen from the S i values, V oc and R 0 are the two, which have the best identifiability among all the six parameters, establishing sufficient confidence for us to use the estimates of these two parameters in battery diagnostic and control applications. This is also discovered by Guo et al through a global sensitivity analysis of second order ECM parameters . Table further shows that the identifiability of these two parameters tends to be much better in the dynamic operating conditions.…”
Section: Results Analysis and Discussionsupporting
confidence: 64%
“…This is also discovered by Guo et al through a global sensitivity analysis of second order ECM parameters. 22 Table 1 further shows that the identifiability of these two parameters tends to be much better in the dynamic operating conditions. On the other hand, it can be observed that the true value of V oc falls within its estimated CIs in both operating cycles.…”
Section: Identifiability Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Based on the anode potential results and engineering experience, the lithium‐ion battery could accept large current at low SOC, 3,18 so the constant dQ/dV could be combined with a large constant current (CC) charge at low SOC to shorten the charging time, as shown in Figure 2B. Since every dQ/dV step could be a constant voltage configuration, the current shows a decreased shape for each step, which could be explained by the first‐ or second‐order model of battery 31 . The inflection point of the current is always around 40% SOC regardless of the value of dQ/dV and the initial current, so we suspect that it is related to the battery characteristics, and the constant current stage should not exceed SOC at inflection point.…”
Section: Methodsmentioning
confidence: 99%